Electricity price and industrial green productivity: Does the "low-electricity price trap" exist?. (15th September 2020) - Ai, Hongshan; Xiong, Shiya; Li, Ke; Jia, Pinrong
Abstract: To explore the existence of the "low-electricity price trap", based on data of 280 cities in China from 2003 to 2015, first, we calculated the Malmquist productivity index and Malmquist-Luenberger Productivity Index, which were used to measure the growth rate of industrial total factor productivity (TFP) and industrial green total factor productivity (GTFP). Then the impacts of industrial electricity price on these metrics were investigated. The results showed that the increase in industrial electricity price would not inhibit development of enterprises by increasing energy costs, but would promote improvement of GTFP, which proved that the "low-electricity price trap" did exist. The higher the level of the industrial electricity price, the stronger the promotion effect. Additionally, these effects showed region heterogeneities, and they were observed highest in the east and lowest in the west. The mechanism analysis showed that although enhancing in industrial electricity price increased the energy cost of enterprises, it could force the enterprises to carry out technological innovation, improve technical efficiency, and ultimately improve GTFP. All the above results were supported by a series of robust tests. Highlights: The"low-electricity price trap" did exist in 280 Chinese cities from 2003 to 2014. Electricity price had a significant positive effect on green total factor productivity. Lowering industrial electricity price is not conducive to improve TFP or green TFP.